THE EMERGENCE OF NIGER DELTA AGITATION FILMS IN NOLLYWOOD: A CRITICAL ANALYSIS OF SELECTED WORKS - Harold Idaerefaka Fyneface (Universitas PGRI Madiun, 2022)
: The Niger Delta region has for some time been at the forefront of the struggle for resource control in Nigeria. Starting from the pre-colonial times till date, the region has been characteristically known for this problem, with a lot of unprecedented consequences ranging from fights between the restive youths and community heads on the one hand and the Nigerian government and the multinational oil companies on the other. It is the nature of this crisis that some films depict in what this study identifies as